Two Islamic Writing Traditions in Southeast Asia: Kitab Jawi and Kitab Kuning with Reference to the Works of Da’ud al-Fatani dan Nawawi al-Bantani - Jajat Burhanudin (Al-Jami'ah Research Centre, 2022)
In reference to the works of two leading ‘ulama of 19th century Southeast Asia, Da’ud al-Fatani and Nawawi al-Bantani, this article discusses the establishment of two Islamic writing traditions, the Malay kitab Jawi and the Arabic kitab which turned to be called more recently as kitab kuning. In spite of the same experiences learning in Mecca, Da’ud al-Fatani wrote his works in Malay, while Nawawi al-Bantani’s kitab were in Arabic. These two writing traditions contributed to the formation of Islamic knowledge among the Muslims of the period, leading the two ‘ulama emerged as the intellectual fathers of Islamic dynamics in respectively Patani-Malaya and Java in Indonesia. In addition to the reason and the ways the two ‘ulama wrote their works in in two different writing styles, other point to highlight is that these kitab Jawi and kitab kuning grew alongside the rise of different Islamic leadership in two major Muslim areas in the region.Artikel ini membahas dua kitab kuning berbahasa Melayu Jawa dan Arab di Asia Tenggara yang merupakan karya Da’ud al-Fatani dan Nawawi al-Bantani. Da’ud al-Fatani menulis dalam bahasa Melayu, sedangkan Nawawi menulis kitab dalam bahasa Arab meskipun keduanya sama-sama belajar agama di Mekkah. Dua kitab ini berkontribusi dalam formasi pembentukan pengetahuan keislaman muslim di Asia Tenggara dan kedua orang tersebut menjadi pembimbing kemunculan dinamika intelektual di Patani dan Jawa abad 19. Keduanya juga hidup di masa kepemimpinan Islam mayoritas yang berbeda wilayah yang mempunyai peran penting dalam pemilihan bahasa, semacam liberasi kognitif, dalam gerakan sosial keagamaan. Penulisan kitab ini bukan sekedar kegelisahan intelektual semata, tetapi mengakar kuat dalam sikap mental yang dominan dalam karakter kepemimpinan Malayu dan Jawa Islam.